PERLINDUNGAN HUKUM TERHADAP SATWA LANGKA DALAM SISITIM HUKUM PIDANA INDONESIA - Andi Purnawati; Irmawaty Ambo (Maleo Law Journal, 2020)
Legal protection in the field of biological conservation and endangered species as part of environmental law, has special characteristics that are different from other types of law. The difference is that the field of law is in the fields of administrative law, civil law and criminal law. This implies that in the case of the imposition of sanctions concerning this field, it can take the form of administrative sanctions (revocation of licenses), criminal sanctions (corporal punishment, fines or both) and civil sanctions (compensation payments and environmental restoration). Legal protection is an activity to protect individuals by harmonizing the relationship of values or rules that are manifested in attitudes and actions in creating order in the association of life among humans. According to Muchsin, legal protection is a matter that protects the legal subject through the applicable laws and regulations and is enforced with a sanction.Keywords: endangered animals, environment and legal protection